PENGEMBANGAN MEDIA ULANGAN HARIAN BERBASIS APLIKASI SMARTPHONE - Haning Hasbiyati; Diah Sudiarti (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2019)
The purpose of daily research media based on smartphone applications is as a solution to optimize the manual daily review system by saving time which is usually used to correct daily tests. At the same time save paper, because it switches to using devices that are not one-time use. So that the application of daily replication applications is expected to be able to improve the quality of education and teaching in the future. The method used in this study is the development or Research and Development (R & D). The product trial subjects consisted of material validators and media validators. In this study, data collection techniques were carried out using a validation sheet. Data analysis in this study is qualitative and quantitative data analysis. In the results of the development of daily media replications based on smartphone applications, the average level of product feasibility of each aspect in terms of material is declared to be feasible at 3.8 and in terms of media is declared feasible at 3.9. So that the daily media review based on smartphone applications deserves to be applied to learning.